Genome‐wide DNA methylation investigation of glucocorticoid exposure within buccal samples. Issue 6 (28th March 2019) - Braun, Patricia R.; Tanaka‐Sahker, Mai; Chan, Aubrey C.; Jellison, Sydney S.; Klisares, Mason J.; Hing, Benjamin W.; Shabbir, Yaseen; Gaul, Lindsey N.; Nagahama, Yasunori; Robles, Julian; Heinzman, Jonathan T.; Sabbagh, Sayeh; et al.
Abstract : Aim: Glucocorticoids play a major role in regulating the stress response, and an imbalance of glucocorticoids has been implicated in stress‐related disorders. Within mouse models, CpGs across the genome have been shown to be differentially methylated in response to glucocorticoid treatment, and using the Infinium 27K array, it was shown that humans given synthetic glucocorticoids had DNA methylation (DNAm) changes in blood. However, further investigation of the extent to which glucocorticoids affect DNAm across a larger proportion of the genome is needed. Methods: Buccal samples were collected before and after synthetic glucocorticoid treatment in the context of a dental procedure. This included 30 tooth extraction surgery patients who received 10 mg of dexamethasone. Genome‐wide DNAm was assessed with the Infinium HumanMethylationEPIC array. Results: Five CpGs showed genome‐wide significant DNAm changes that were >10%. These differentially methylated CpGs were in or nearest the following genes: ZNF438, KLHDC10, miR‐544 or CRABP1, DPH5, and WDFY2 . Using previously published datasets of human blood gene expression changes following dexamethasone exposure, a significant proportion of genes with false‐discovery‐rate‐adjusted significant CpGs were also differentially expressed. A pathway analysis of the genes with false‐discovery‐rate‐adjusted significant CpGs revealed significant enrichment of olfactory transduction, pentose and glucuronate interconversions, ascorbate and aldarate metabolism, and steroid hormone biosynthesis pathways. Conclusion: High‐dose synthetic glucocorticoid administration in the setting of a dental procedure was significantly associated with DNAm changes within buccal samples. These findings are consistent with prior findings of an influence of glucocorticoids on DNAm in humans.